Kumpulan Kitab Undang² Hukum Disiplin Tentera, Kitab Undang² Hukum Pidana Tentera dan Hukum Acara Pidana Tentera (s.n., 1974)
Disciplinary, criminal, and criminal procedural laws for Indonesian militaries and policemen.